PENGARUH KOMPETENSI GURU PENDIDIKAN AGAMA KRISTEN TERHADAP HASIL BELAJAR PESERTA DIDIK DI SMA NEGERI 4 KOTA KUPANG - Hendrik AE Lao; Obed Oktofianus Maudemang (Institut Agama Kristen Negeri (IAKN) Ambon, 2022)
The learning conduct at school is done so that all students can get satisfying learning outcomes. Some efforts to improve student learning outcomes are increasing teacher’s competence and student’s intelligence. The objectives of this study are to analyze the effect of teacher’s competence on student’s learning outcomes. The study was conducted at four Public High Schools in Kupang. In this study, the author used a quantitative approach using correlative research methods. The population in this study were all Christian student’s sitting in class XI Social Sciences Education (IPS) as many as 152 people. This research took 20% of the total population (30 student’s). As sample usiup the Simple Random Sampling. Data collection od using questionnaires. Data analysis techniques used simple linear regression equations with Pearson correlation formula. The results showed there was no significant effect of christian religion teacher competence on student learning outcomes of 2.4%. The conclusion of the research is the teacher's competence does not have a significant effect on student learning outcomes.Keywords: Teacher Competence, student and learning out comes